2017
DOI: 10.24820/ark.5550190.p010.023
|View full text |Cite
|
Sign up to set email alerts
|

Fast highly efficient 'on-solvent' non catalytic cascade transformation of benzaldehydes and 4-hydroxycoumarin into bis(4-hydroxycoumarinyl)arylmethanes

Abstract: Non-catalytic cascade reaction of benzaldehydes and two equivalents of 4-hydroxycoumarin initiated by reflux in propanol results in the fast (15 min) and efficient formation of substituted tetrahydro-1H-xanthen-1-ones in 93-98% yields. The developed fast cascade approach to the substituted bis(4-hydroxycoumarinyl)arylmethanes, which are known as medicinally relevant substances with anti-HIV, antibiotic, anti-inflammatory and anti-cancer activity, is beneficial from the viewpoint of diversity-oriented large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…There are some publications on the synthesis of dicoumarols in the presence of 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) as non-nucleophilic and strong tertiary amine base [30], in phosphoroxychloride in dry DMF [31], in refluxing ethanol and acetic acid [27,[32][33][34][35], under microwave irradiation in ethanol or solvent-free conditions [32], in the presence of diethylaluminum chloride (Et 2 AlCl) in dichloromethane [36], in the presence of catalytic amount of piperidine in ethanol [37] or other polar solvents like methanol, dimethylformamide or dimethyl sulfoxide at room temperature [38], and using triethylamine in methanol or sodium ethoxide in ethanol in the presence of cyanogen bromide [39]. It was also published some uncatalyzed onepot synthesis of dicoumarols under conventional or microwave thermal solvent-free conditions, which is a simple, practical, and environmentally benign method to obtain dicoumarols in excellent yields [30,40,41] as well as the catalyst-free one-pot synthesis in water under ultrasounds irradiation at ambient temperature [42] or the "on solvent" reaction using minimal amount of boiling propanol without any catalyst [43]. In 2012, Mallik and coworkers developed an "on water" methodology for the synthesis of dicoumarols at 95 °C for 4-5 h. In their study, they observed a significant reduction of reaction time from 4-5 h to 0.5 h, if an electrolyte was added to the reaction.…”
Section: Catalyst-free Synthesis and Synthesis Using Homogeneous Cata...mentioning
confidence: 99%
“…There are some publications on the synthesis of dicoumarols in the presence of 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) as non-nucleophilic and strong tertiary amine base [30], in phosphoroxychloride in dry DMF [31], in refluxing ethanol and acetic acid [27,[32][33][34][35], under microwave irradiation in ethanol or solvent-free conditions [32], in the presence of diethylaluminum chloride (Et 2 AlCl) in dichloromethane [36], in the presence of catalytic amount of piperidine in ethanol [37] or other polar solvents like methanol, dimethylformamide or dimethyl sulfoxide at room temperature [38], and using triethylamine in methanol or sodium ethoxide in ethanol in the presence of cyanogen bromide [39]. It was also published some uncatalyzed onepot synthesis of dicoumarols under conventional or microwave thermal solvent-free conditions, which is a simple, practical, and environmentally benign method to obtain dicoumarols in excellent yields [30,40,41] as well as the catalyst-free one-pot synthesis in water under ultrasounds irradiation at ambient temperature [42] or the "on solvent" reaction using minimal amount of boiling propanol without any catalyst [43]. In 2012, Mallik and coworkers developed an "on water" methodology for the synthesis of dicoumarols at 95 °C for 4-5 h. In their study, they observed a significant reduction of reaction time from 4-5 h to 0.5 h, if an electrolyte was added to the reaction.…”
Section: Catalyst-free Synthesis and Synthesis Using Homogeneous Cata...mentioning
confidence: 99%